(untitled) (Research, Society and Development, 2021)
Fish can be contaminated in the environment in which they live or during handling after a catch. A bacterial species Vibrio parahaemolyticus is one of the main causes of outbreaks associated with the consumption of contaminated fish. Essential oils used in food preparation due to their different flavor and aroma. The essential oil of Origanum vulgare stands out for its ability to inhibit the growth of unwanted microorganisms. Toppings containing essential oil have gained recognition lately. The aim of the study was to evaluate an antimicrobial activity of O. vulgare essential oil associated with an edible starch coating in fish fillet. The effect of O. Vulgare oil was tested in vitro by disk-diffusion test. Subsequently, starch coating with 1% and 1.5% of O. vulgare essential oil was applied to M. furnieri fillets experimentally contaminated with V. parahaemolyticus. As a control, uncoated and oil-free coated fillets were also tested. Counts of V. parahaemolyticus were performed after 0, 1, 2, 3, 4, 5 and 10 days of storage. In the disk-diffusion test, the essential oil of O. vulgare showed an inhibitory effect on bacterial growth. Starch coating associated with O. vulgare essential oil was efficient to reduce bacterial multiplication in fish fillets in the two tools used in the study. The use of starch coating with O. vulgare essential oil to control V. parahaemolyticus in fish is a promising alternative for safe food consumption.